Sistema mobile para unidades prisionais do estado do Rio Grande do Norte – Infosisp mobile - Queiróz Neto, Antonio (Universidade Federal Rural do Semi-Árido, 2017)
In the Penitentiary System of the Rio Grande do Norte State, counting the inmates, one of the most trivial activities in a prison unity, and at a first glance simple, may unfold costly when the proper tools are not provided. Based on this problem, it was proposed the development of an application for mobile devices, using the appropriate software engineering techniques, which will help the prison agents in such activity. This paper will present the development and validation proceedings for a tool that will improve the control in the inner movement of the inmates, and so the results obtained. The system was tested on the Cadeia Pública de Caraúbas by real prison agents who may effectively come to use it
Monografia
Keywords: Sistema penitenciário; Engenharia de software; Modelo de aceitação; INFOSISP Mobile; Penitentiary System; Softer Engineering; Acceptance Model; INFOSISP Mobile; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO